Evaluating the effect of soil structure on the ground response during shield tunnelling in Shanghai soft clay. (September 2016) - Bian, Xia; Hong, Zhen-Shun; Ding, Jian-Wen
Highlights: We proposed a model incorporating soil structure that is suitable for tunnel analyses in Shanghai soft clay. Effect of soil structure on tunnel induced ground response and long-term behaviour was evaluated. The mechanism of the effect of soil structure on ground response was discussed. Abstract: When evaluating tunnel-induced ground response in Shanghai soft clay, the soil structure and its degradation behaviour of natural Shanghai soft clay during shield tunnelling should be properly considered. In this paper, a constitutive model that considers the initial soil structure and its destructuration is formulated within the framework of critical-state soil mechanics. The model is successfully calibrated and used to simulate the undrained behaviour of natural Shanghai soft clay. Based on the proposed model, finite-element analyses are conducted to simulate the short- and long-term ground responses induced by tunnelling at Shanghai metro line 2. The comparisons between numerical results and field measurements reported in literature indicate that the soil structure and the tunnel-induced destructuration significantly affects the magnitude and shape of the short-term surface settlement trough and horizontal displacement in Shanghai soft clay. The pore pressure variations around the tunnel are also affected by soil structure, which will significantly influence the long-term ground consolidation settlement in Shanghai soft clay.